Monetary Policy Response in the Republic of North Macedonia and the Republic of Albania for Coping with the Pandemic COVID-19 in 2020 - Alba Pollozhani; Shenaj Hadzimustafa (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2021)
This study aims to analyse how the monetary policies of the Republic of North Macedonia and the Republic of Albania, as one of the two critical macroeconomic policies, have reacted in response to COVID-19 for the year 2020. Last year, the year 2020, the pandemic caused these two countries to react through monetary policy. This research examines how central banks of both countries have changed traditional monetary policy tools for tackling the pandemic, starting with open market operations, required reserve ratio, the overnight loans interest rate, and the available deposits interest rate. The research continues with analyzing whether they were used and what non-traditional tools were applied in that period. The study analysis concludes which monetary policies have been pursued in the Republic of North Macedonia and the Republic of Albania, whether there have been non-traditional tools and how the scope for interbank interest rate volatility has changed. Our study revealed that both countries had pursued an expansive monetary policy, there were also non-traditional tools, and the scope for interbank interest rate volatility has shifted towards narrowing.
Keywords: E49; E58; E59; 330; monetary policy; central bank; traditional tools; non-traditional tools; interbank interest rate